Alterations in iron levels in Japanese encephalitis virus infection. - Mathur, A. (1990)
Following Japanese encephalitis virus (JEV) infection in mice the serum iron concentration decreased; the decline started from day 3 and persisted up to day 9 postinfection. No significant difference was found in the total iron-binding capacity of serum in JEV-infected mice compared with that of controls. The hypoferraemia was associated with accumulation of iron in the spleen. Large amounts of stainable iron were demonstrated in splenic macrophages from day 5. This was accompanied by transient anaemia. Thus, the hypoferraemia, following intraperitoneal inoculation of JEV, was attributed to a block in the release of iron from the RES.